2019
DOI: 10.1101/19011866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction patients with diabetes mellitus and its association with body mass index and glycated hemoglobin in Africa: a systematic review and meta-analysis

Abstract: Background: Mortality and morbidity in patients with diabetes mellitus (DM) is attributed to both the micro vascular and macro vascular complications. Variation among primary studies was seen on the prevalence of erectile dysfunction in Africa. Therefore this study was aimed to estimate the pooled prevalence of erectile dysfunction patients with diabetes mellitus and its association with body mass index and glycated hemoglobin in Africa. Methods: PubMed Web of Science Cochrane library Scopus Psyinfo Africa onl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…The methodological and overall quality of each article was assessed by both authors based on the modified version of the Newcastle-Ottawa Scale (NOS) for cross-sectional studies [31]. Studies which scored ≥5 out of 10 points in three domains of the modified NOS for a cross-sectional study were included in the analysis [32]. Any disagreements at the time of data abstraction were reconciled by discussion and consensus, (Supplementary file 1).…”
Section: Selection and Quality Assessmentmentioning
confidence: 99%
“…The methodological and overall quality of each article was assessed by both authors based on the modified version of the Newcastle-Ottawa Scale (NOS) for cross-sectional studies [31]. Studies which scored ≥5 out of 10 points in three domains of the modified NOS for a cross-sectional study were included in the analysis [32]. Any disagreements at the time of data abstraction were reconciled by discussion and consensus, (Supplementary file 1).…”
Section: Selection and Quality Assessmentmentioning
confidence: 99%
“…Worldwide the burden of ED is huge with projected prevalence estimated to be around 322 million by 2025. [ 3 4 ] Previously available literature documents higher rates of ED in United States (US) and Asia than the rest of the world. [ 5 ] According to the projected estimates, Asia will have 200 million men suffering from ED, reflecting a 130% growth in 2025.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of ED in this systematic review and meta-analysis was lower than the findings from a systematic review and meta-analysis done globally (59.1%) 19 and in Africa (71.45%). 7 This disparity might be owing to differences in the number of study participants. The number of patients in the current systematic review and meta-analysis was low compared with those previous two reviews, which might contribute to the lower prevalence of ED in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In Africa, evidence from a systematic review and meta-analysis showed that the ED prevalence ranges from 36% to 95%, with pooled prevalence of 71.45%. 7 In Ethiopia, the prevalence of ED among patients with diabetes ranges from 6.8% to 85.5%. 8,9 ED can stem from organic causes including hormone-induced, drug-induced, vascular, traumatic or post-surgical, and psychogenic causes including depression, relationship problems, and performance anxiety.…”
Section: Introductionmentioning
confidence: 99%